Analisis Pengaruh Pemanfaatan Sistem Informasi Manajemen Pada Layanan Kesehatan Rumah Sakit: Literature Review - Fladyan Grace Wulur; Ida Fitriyani; Vip Paramarta (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
Hospitals certainly have strategic policy formulation in internal parts, especially organization, management and human resources (HR) and must be able to make decisions effectively to improve the quality of health services. So by increasing this vision it is necessary to use information management systems in hospital services. Health services are the main topic because of the high complexity of challenges in the health sector. The purpose of this study was to determine the Implementation of the Hospital Management Information System (SIMRS) in the influence of SIMRS on health services. With various service management information systems and different features, it is necessary to have regulations and make minimum standards that must be set by the ministry of health in order to achieve uniform services and be able to carry out full electronic-based activities, the need for the capacity of the ministry of health to provide applications for hospitals that are still unfamiliar with SIMRS and ongoing training and need more monitoring. The research design used in the preparation of this article is a literature review method related to Hospital Management Information Systems in Health Services. Search results using several databases such as Scopus, Google Scholar and also by collecting information that has been obtained from online journal article literature sourced from reference books and books related to the topic. The results of 8 articles obtained that the Effect of Utilizing Management Information Systems on Health Services in Hospitals by increasing Human Resources (HR), Standard Operating Procedures (SOP) for Facilities and Infrastructure, Implementation of Hospital Management Information Systems (SIMRS), Improving the Quality of Health Services, and Hospital Promotion and Service Policy. It can be concluded that the management information system in health services is something that integrates the entire process flow of hospital services in the form of a network that improves human resources for health services, quality information systems in hospitals. This strategy becomes an arrangement or equipment that provides information to develop to achieve the objectives of its activities.